Thermally driven phase transition of cobalt hydroxide sheets via cobalt oxides to cobalt nanoparticles. Issue 10 (5th August 2022) - Yoon, Aram; Kim, Gyutae; Lee, Minjeong; Lee, Zonghoon; Ryu, Gyoeng Hee
Abstract : We investigated phase transitions of Co(OH)2 nanosheets by in situ scanning transmission electron microscopy heating experiments. The layered Co(OH)2 transformed to Co nanoparticles via CoO phases; spinel Co3 O4 was formed with temperature reduction. Abstract : Transition metal oxides, which include many stoichiometric variations, are formed into various crystal structures by the atomic arrangement of cations and anions according to stoichiometric composition and are used for a wide range of applications based on this. Among them, cobalt oxide, which has wide crystal structures depending on the lattice points of the anion and the valence of the Co cation, from its hydroxide formula, is attracting a lot of attention due to its interesting catalytic properties due to its crystal structure. In this study, using the synthesized Co(OH)2 nanosheets, the real-time behavior of the phase transition that occurs when continuous heat is applied to the sample has been systematically analyzed using an aberration-corrected scanning transmission electron microscope. The layered Co(OH)2 phase passes through hexagonal CoO and cubic CoO phases to finally become Co nanoparticles, but when the temperature is dropped in the hexagonal phase, spinel Co3 O4 is formed. These results suggest that various phases included in transition metal oxides can be selectively implemented according to temperature range control.